Serum amyloid protein A concentration in cryopyrin-associated periodic syndromes patients treated with interleukin-1 beta antagonist. - Pastore, Serena; Paloni, Giulia; Caorsi, Roberta; Ronfani, Luca; Taddio, Andrea; Lepore, Loredana (Clin Exp Rheumatol, 2014)
OBJECTIVES: Cryopyrin-associated periodic syndromes (CAPS) are a group of chronic, relapsing autoinflammatory disorders which may be complicated by systemic AA amyloidosis. The aim of our study was to evaluate serum amyloid protein A (SAA) level in CAPS patients treated with Interleukin-1beta (IL-1β) antagonist and to correlate its level with treatment response. METHODS: All patients of CAPS Italian Register treated with IL-1β inhibitor were enrolled. SAA levels before starting therapy, and at last visit were evaluated. Patients were then divided in complete responders and partial responders. RESULTS: Twenty-five patients were enrolled. SAA level before starting therapy was increased (median 118.5 mg/L, IQR 96.4-252.8; normal value <6.4 mg/L), while at last visit SAA was significantly reduced (median 4.3 mg/L, IQR 2.3-12.7) (p<0.001). However 12 patients still presented SAA levels beyond normal range, 10/25 patients (40%) showed a complete response to treatment. Conversely, 15 patients presented only a partial response, of which 12 for increased SAA value and 3 for increased CRP value. Patients with partial response had SAA values significantly higher than patients with complete response (median 12.6 mg/L; IQR 8.3-20.0 vs. 2.7 mg/L; IQR 1.6-4.1, p<0.001). CONCLUSIONS: Our results confirm the long term efficacy of anti IL-1β treatment in CAPS and the decrease of SAA levels; however 48% of patients still presented SAA elevation despite treatment. The real risk of these patients in developing amyloidosis is not clear but the persistent increase of SAA needs a close follow-up.
Keywords: Adolescent; Adult; Amyloidosis; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Drug Monitoring; Female; Humans; Immunosuppressive Agents; Interleukin-1beta; Male; Middle Aged; Serum Amyloid A Protein; Treatment Outcome; Young Adult